Pathways to Hazardous Drinking Among Racially and Socioeconomically Diverse Lesbian Women: Sexual Minority Stress, Rumination, Social Isolation, and Drinking to Cope. (December 2016) - Lewis, Robin J.; Mason, Tyler B.; Winstead, Barbara A.; Gaskins, Melissa; Irons, Lance B.
Lesbian women engage in more hazardous drinking than heterosexual women yet we know relatively little about what explains this disparity. In the present study, race, socioeconomic status (SES), minority stress, general psychological processes, and distress were examined as pathways to hazardous drinking among young (18–35 years) Black and non-Hispanic White lesbian women. We used the psychological mediation framework adaptation of minority stress theory and the reserve capacity model as theoretical underpinnings of the conceptual model in the current study. Self-identified lesbian participants ( N = 867) completed a onetime online survey that assessed race, SES, perceived sexual minority discrimination, proximal minority stress (concealment, internalized homophobia, lack of connection to lesbian community), rumination, social isolation, psychological distress, drinking to cope, and hazardous drinking. Cross-sectional results demonstrated that being Black was associated with hazardous drinking via sequential mediators of rumination, psychological distress, and drinking to cope. SES was associated with hazardous drinking via sequential mediators of sexual minority discrimination, proximal minority stress, rumination, social isolation, psychological distress, and drinking to cope. Understanding these pathways can aid researchers and clinicians studying and working with lesbians who are at risk for hazardous drinking.